Daoism as the Philosophic Foundation of Chinese Economic Reform: a Conjecture - Edward J Romar (Emerging Science Journal, 2018)
The reforms of Deng Xiaoping and the opening of China in the 1970s were predicated on something called “socialism with Chinese Characteristics”. Deng never explained its meaning in detail. This paper offers a conjecture suggesting that Daoism is the philosophical foundation of Chinese economic reform. Daoism is eminently Chinese and through the concepts of wu wei, yin/yang, qi and others from The Tao Te Ching, the Zhuangzi, and Pheasant Cap Master it offers the flexibility to organize markets within the Chinese context. The paper suggests how a Daoist philosophic foundation supports China’s rise both economically and politically. It concludes with the observation that China’s long term objective may be something like Zhuangzi’s and Pheasant Cap Master’s unity and that the West’s “end of history” may have past while the Chinese may have just begun.(B)y Marxism we mean Marxism that is integrated with Chinese conditions, and by socialism we mean a socialism that is tailored to Chinese conditions and has a specifically Chinese character….Socialism means eliminating poverty. Pauperism is not socialism, still less communism (Deng Xiaoping, Socialism with Chinese Characteristics [1]).…China’s rise is not the rise of an ordinary state, but the rise of a country, sui generis, a civilizational state, a new model of development and a new political discourse which questions many of the Western assumptions about democracy, good governance and human rights, and all this may usher in a wave of change unprecedented in human history. Zhang Weiwei, The China Wave [2]).